Analisis Kemampuan Menggiring Bola Dalam Permainan Sepakbola - Ricardo Valentino; M. Irfan Hasanuddin (Departement of Mathematics Education, 2023)
This research is a quantitative descriptive study that aims to determine the level of dribbling skills in the soccer game on the Rappocini State Elementary School soccer team. The population in this study was the entire football team at SD Negeri Rappocini, totaling 20 students, while the sample in this study was 20 students, with the sampling technique using total sampling (saturated sampling). The results of data analysis are students in the